2013
DOI: 10.1007/s00417-013-2463-8
|View full text |Cite
|
Sign up to set email alerts
|

Branch retinal vein occlusion and vitreovascular traction: a preliminary spectral domain OCT case–control study

Abstract: A common firm vitreous adhesion at the obstruction site is reported herein, pointing out the possible role of vitreovascular traction in the etiology of some cases of BRVO. Likewise, although not all BRVO cases can be explained by this pathogenic mechanism, an attached posterior vitreous cortex might be a cofactor in the origin of this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Although the pathogenesis of ME when associated with RVO (RVO-ME) is not fully understood, increased rigidity of a crossing artery as a result of an atherosclerotic process has been suggested to cause compression of the underlying vein, provoking turbulent blood flow, endothelial damage, and thrombus formation [ 11 ]. Likewise, a common vitreous adhesion at the obstruction site has also been reported, suggesting a possible role of vitreovascular traction in the etiology of some cases of BRVO [ 12 , 13 ].…”
Section: Macular Edema: a Nonspecific Indication Of Numerous Retinmentioning
confidence: 99%
“…Although the pathogenesis of ME when associated with RVO (RVO-ME) is not fully understood, increased rigidity of a crossing artery as a result of an atherosclerotic process has been suggested to cause compression of the underlying vein, provoking turbulent blood flow, endothelial damage, and thrombus formation [ 11 ]. Likewise, a common vitreous adhesion at the obstruction site has also been reported, suggesting a possible role of vitreovascular traction in the etiology of some cases of BRVO [ 12 , 13 ].…”
Section: Macular Edema: a Nonspecific Indication Of Numerous Retinmentioning
confidence: 99%
“…A subsequent study done by Avunduk et al 11 in 1997 indicated that a total PVD reduced the incidence and persistence of both retinal neovascularization and ME in eyes with RVO. These studies provide precedence in investigating the use of modern clinical diagnostics and treatments that could induce PVD to inhibit persistent ME secondary to RVO 12 13…”
Section: Introductionmentioning
confidence: 99%
“…Direct association between these noncentral extrafoveal tractional membranes and the central macular edema was confirmed by using the full-field 3-D SD-OCT approach that included 360° viewing of the examined fields by video clips, as documented 1,2 and summarized. 3 Such association was later reported by others in DME 4 and BRVO. 5 Nowadays, new OCTs enable 3-D wide-field imaging, which would facilitate diagnosis of noncentral trac-tion and its association with the central macula pathology.…”
Section: Dear Editormentioning
confidence: 53%